An Increase in Kinematic Freedom in the Lokomat Is Related to the Ability to Elicit a Physiological Muscle Activity Pattern: A Secondary Data Analysis Investigating Differences Between Guidance Force, Path Control, and FreeD - Aurich-Schuler, Tabea; Labruyère, Rob (Frontiers in Robotics and AI, 2019)
Background: Robot-assisted gait therapy is a fast-growing field in pediatric neuro-rehabilitation. Understanding how these constantly developing technologies work is a prerequisite for shaping clinical application. For the Lokomat, two new features are supposed to increase patients’ movement variability and should enable a more physiological gait pattern: Path Control and FreeD. This work provides a secondary data analysis of a previously published study, and looks at surface electromyography (sEMG) during Guidance Force walking and six sub-conditions of Path Control and FreeD. Objective: The aim was to further explore the technology by modulating the settings in Path Control and FreeD. Methods: Fifteen patients (mean age 16±2 y) with neurological gait disorders completed the measurements. We analyzed sEMG patterns of 5 leg muscles during walking conditions with increasing kinematic freedom. The new outcome measure of inter-step similarity is introduced as a proxy for walking difficulty. Results: With increasing kinematic freedom, Path Control sub-conditions showed significantly higher sEMG amplitudes (except for M.gastrocnemius lateralis) and larger correlations with the norm pattern. FreeD sub-conditions generally showed a low inter-step similarity. Conclusions: In general, this work highlights that the new hard- and software approaches of the Lokomat influence muscle activity differently. An increase of kinematic freedom of the walking condition led to an increase in muscular effort (Path Control) or to a higher step variability (FreeD) which can be interpreted as an increased difficulty of this condition. The inter-step similarity could be a helpful tool for the therapist to estimate the patient’s state of strain.